KONTRIBUSI NAHDLATUL ULAMA TERHADAP PEMIKIRAN ISLAM MODERAT DI INDONESIA - Faiza Nur Khalida; Kaesul Ma’arif; Saripah; Agus Gunawan; Iffan Ahmad Gufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Moderate Islam is regarded as a middle ground between overly conservative and overly liberal attitudes. This approach highlights the importance of implementing Islamic teachings that consider humanitarian values and social harmony, such as peace, tolerance, and respect for diversity. This article aims to analyze the contributions of Nahdlatul Ulama to moderate Islamic thought in Indonesia, focusing on how the organization formulates the concept of religious moderation and its influence on social, political, and religious developments in Indonesia. The research method employed by the researcher is qualitative, using a literature study approach. The research findings indicate that Nahdlatul Ulama (NU) has a significant contribution to the development of moderate Islamic thought in Indonesia, manifested through various fields such as education, politics, social issues, and preaching. In education, NU introduces a curriculum that integrates Islamic teachings with local values, focusing on character development that reflects moderation, tolerance, and pluralism. In the political and social realms, NU plays a role in promoting stability and diversity through moderate attitudes, as well as actively engaging in public policy advocacy that supports tolerance and national unity. NU's social and preaching movements strive to build a harmonious society through economic empowerment programs, humanitarian activities, and interfaith dialogue. NU also has strategic policies to reject extremism by promoting religious moderation, enhancing public understanding, and creating constructive dialogue spaces.